2006
DOI: 10.1007/bf03026818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diazepam on125I-iomazenil-benzodiazepine receptor binding and epileptic seizures in the El mouse

Abstract: The results suggest that diazepam binds competitively to 125I-IMZ as an agonist to free benzodiazepine receptor sites in the cortex, hippocampus and amygdala and shows anticonvulsant effect in E1 mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The present study is useful in showing that sodium valproate or diazepam attenuates the EEG changes induced by oral oseltamivir administration in El mice. Several AEDs are known to reduce the frequency of seizures [8,9], but to the best of our knowledge no previous studies have electrophysiologically demonstrated the efficacy of AEDs in El mice. The present study suggests that short-term supplemental administration of sodium valproate or diazepam may be considered as an option in patients with epileptogenic tendencies (past history of febrile and/or non-febrile seizures) but not on a regular daily course of AEDs, who are taking oseltamivir phosphate.…”
Section: Discussionmentioning
confidence: 96%
“…The present study is useful in showing that sodium valproate or diazepam attenuates the EEG changes induced by oral oseltamivir administration in El mice. Several AEDs are known to reduce the frequency of seizures [8,9], but to the best of our knowledge no previous studies have electrophysiologically demonstrated the efficacy of AEDs in El mice. The present study suggests that short-term supplemental administration of sodium valproate or diazepam may be considered as an option in patients with epileptogenic tendencies (past history of febrile and/or non-febrile seizures) but not on a regular daily course of AEDs, who are taking oseltamivir phosphate.…”
Section: Discussionmentioning
confidence: 96%